PERBEDAAN SPESIFIC VALUES ANTARA MAHASISWA AKUNTANSI DAN MAHASISWA KEDOKTERAN: STUDI EMPIRIS PADA UNIVERSITAS GADJAH MADA - Fathonah, Siti (Journal of Indonesian Economy and Business, 2004)
This study aims to analyze, to compare and to differentiate specific values of accountingand medical students. While the majority of previous studies used the Rokeach InstrumentSurvey, the current study employs the modified Rokeach and Schwartz Instrument. Thismodified instrument consists of thirty variables. However, a factor analysis indicates thatthe variables can be grouped into four constructs: individuality, theoretical, social, andesthetical. Overall, the study shows that personal values of accounting students are belowthose of medical students. Based on the finding, the study suggests that a certain subject orcourse with a high ethical contents should be taught in accounting programs.Keywords: etika, specific values, personal values, individuality, theoretical, social,aesthetics